Perkembangan Bahasa Indonesia di Era Digital: Tantangan dan Peluang bagi Siswa Membangun Fondasi Bahasa di Era Revolusi Digital - Peranginangin, Yunita; Ritonga, Zakia; Sion Br Siallagan, Putri; Surip, M (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The development of digital technology has created a significant impact on the use of Indonesian, especially among students. Easy access to social media, chat applications, and digital learning platforms have changed the way students communicate and interact. On the one hand, the digital era offers advantages in the form of increased access to learning and creativity in language, but on the other hand, challenges also arise, such as the increasing use of everyday language, abbreviations that are not in accordance with the rules, and excessive acceptance of foreign terms. This study aims to investigate how the evolution of Indonesian in the digital era affects students at SMP Negeri 7 Medan and the role of teachers in guiding them to continue using correct and good Indonesian. By applying a qualitative approach through literature research and interview analysis, this study found that teachers face various difficulties in maintaining the use of Indonesian according to the rules amidst digital developments. With the right strategy, the digital era can be an opportunity to strengthen the use of Indonesian among students.